Initial Impact of an Educational Program Programme for the Orphans in Erbil City - Bushra Rashid; Zainab Yalman Othman (Eurasian Journal of Science and Engineering, 2022)
Purpose: This study aimed to assess the state of the orphans’ oral health living in Erbil orphanage; their oral health knowledge, attitude and practice; and the improvements in oral healthcare after the provision of oral health education. Materials and Methods: The study included orphans aged 6–15 years living in Erbil orphanage in Iraq. As a baseline visit (A), the oral hygiene status of all participating orphans was evaluated using the oral hygiene index–simplified (OHI-S). To evaluate the orphans’ oral health knowledge, attitude and practice, the orphans completed an oral hygiene questionnaire. Dental caries prevalence was assessed using the decayed, missing, filled teeth (DMFT and dmft index). An educational programme was provided which included demonstrations and descriptions of dental health indications and how to carry out oral hygiene procedures. After two months, follow-up visit (B) performed to assess the OHI-S, and the same oral hygiene questionnaire that was used in the baseline visit was also completed by the orphans. Results: Between visits A and B, no significant differences were found in oral health knowledge (visit A = 7.321 ± 2.204 and visit B = 7.714 ± 1.749) or attitude (4.357 ± 2.930 and 4.553 ± 2.992). A significant difference was found in oral health practice (5.15 ± 1.89 and 6.3 ± 1.69). Dental caries prevalence was 65% in the primary teeth and 73% in the permanent teeth. Conclusion: The orphans and caregivers need training in how to maintain oral hygiene. Dental health professionals should provide oral health education and regular screening camps for these children.